Teacher professional development in Teaching and Teacher Education over ten years - Avalos, Beatrice (Teaching and teacher education, 2011)
A review of publications in Teaching and Teacher Education over ten years (2000–2010) on teacher professional development is the subject of the paper. The first part synthesises production referred to learning, facilitation and collaboration, factors influencing professional development, effectiveness of professional development and issues around the themes. The second part, selects from the production nine articles for closer examination. The paper concludes by noting how the production brings out the complexities of teacher professional learning and how research and development have taken cognisance of these factors and provided food for optimism about their effects, although not yet about their sustainability in time.